Application of The Problem Based Learning Model to Improve Student Learning Activity in Mathematics Learning for Class VII at MTs Madrisatul Ikbar Tembung T.A 2020/2021 - Wulandari, Sri (Lembaga Riset Mutiara Akbar, 2022)
The purpose of this study was to find out how active students are in learning mathematics using a problem-based learning model at MTS Madrisatul Ikbar Tembung. This research method uses classroom action research that follows a problem-based learning model. The data of this study were obtained through tests and observations. The subjects in this study were seventh grade students of MTS Madrisatul Ikbar Tembung. This research was conducted in two cycles, namely cycle I and cycle II. Each cycle has stages, namely: planning, implementation, observation, and reflection. Student improvement data obtained in the field are written in the form of tables and diagrams. After the data was analyzed, several findings were obtained, namely the initial test showed that students' completeness reached 9.09% (1 student), the first cycle reached 36.36% (4 students), and there was an increase of 27.27%, and the second cycle reached 81, 82% (9 students) and an increase of 72.73%. Thus, in the second cycle, students' learning completeness is classically fulfilled because 75%. Based on the results of the study, it can be concluded that the application of the problem-based learning model can increase student learning activity in mathematics learning for students of MTS Madrisatul Ikbar Tembung T.A 2020/2021